2018
DOI: 10.1002/acs.2934
|View full text |Cite
|
Sign up to set email alerts
|

Power sharing adaptive control strategy for a microgrid with multiple storage and renewable energy sources

Abstract: SummaryWith the rapid growth of single‐phase renewable energy source units within three‐phase microgrids, the accuracy of the power sharing per phase among distributed generation (DG) units is necessary. This paper proposes an adaptive power control strategy based on new sliding mode control for islanding operation of a microgrid with multiple three‐phase and single‐phase DGs. The studied microgrid consists of two three‐phase photovoltaic (PV) arrays and three single‐phase DG units, which include PV, fuel cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In [13] an adaptive power control strategy based on sliding mode control is presented for the operation of islanded microgrids. In [14] AGC gain scheduling is implemented with a recursive least square approach combined with a genetic algorithm and a fuzzy system, both utilized to estimate the power system parameters in a real-time.…”
Section: B Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In [13] an adaptive power control strategy based on sliding mode control is presented for the operation of islanded microgrids. In [14] AGC gain scheduling is implemented with a recursive least square approach combined with a genetic algorithm and a fuzzy system, both utilized to estimate the power system parameters in a real-time.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The complement between the optimal value function ( 9), the optimal control (13), and the Q(x i , u i ) in ( 14) is the cornerstone of the proposed model-free policy iteration. The connection between these three equations will lead to obtaining the optimal control signal u • as defined in (13) which presents a solution to the modified Bellman equation. Considering the value function with the optimal policy u • , the value function is written as…”
Section: A Online Adaptive Policy Iterationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the lithium-ion battery is employed in the EVs. According to the Thevenin equivalent circuit model, 31 the battery's state of charge (SOC) and battery regenerative power can be represented, respectively, as follows:…”
Section: Battery Modelmentioning
confidence: 99%
“…The results have shown that the system is not rentable for the winter months due to its low efficiency and costs. In [28], Sedaghati and Shakarami proposed a multiple phase control strategy using fuel cell, battery systems, and photovoltaic panels to establish certain parameters and conditions. The control strategy shows lower steady-state error and faster response.…”
Section: Introductionmentioning
confidence: 99%